O impacto da geração distribuída remota nos investimentos do sistema elétrico de distribuição da CEMIG-D - Raphael Fidelis Bernardes (2021)
In the last few years, it has been more perceptible the spread of small power generations closer to the consumers, from which we can hightlight the solar generation. This sort of generation is called distributed generation and it has many varieties. The distributed micro and minigeration, which represent a trend in Brazil, were studied in this project. This kind of generation helps in the diversification of the eletricity matrix and gives to the owners of the plants a discount in their eletricity bill. However, to the distribution system, this model might be causing the need to antecipate investiments. So, aiming to verify this assumption, this project analyzes the situation of minigeneration in CEMIG-D in the last few years (2017 to 2020), by the regional following of the requests of connections and the need of investiments due to generation connection. Results show that the connection of minigeneration in low load density places brings the need to invest in the electric system of those places.